Green Sukuk as a Sustainable Financing Instrument: Evidence from Indonesia and Malaysia - Mega Ilhamiwati; Ryan Teo; Lucas Wong (Yayasan Adra Karima Hubbi, 2025)
Green Sukuk represents a strategic innovation in Islamic finance that aligns environmental sustainability with Sharia-compliant investment principles. The increasing global urgency to address climate change has driven Muslim-majority nations such as Indonesia and Malaysia to pioneer the issuance of Green Sukuk as a dual-purpose instrument financing sustainable projects while promoting ethical investment behavior. The purpose of this study is to analyze the effectiveness of Green Sukuk in supporting national sustainable development goals and to evaluate its role in strengthening green financial ecosystems. The research employs a mixed-method approach combining document analysis, market data review, and expert interviews from both countries’ financial authorities. The results show that Green Sukuk issuance has significantly contributed to renewable energy and climate-resilient infrastructure projects, enhancing investors’ confidence through transparent reporting and Sharia compliance. Comparative findings reveal that Indonesia focuses on sovereign sustainability frameworks, whereas Malaysia emphasizes private sector innovation and regulatory facilitation. The study concludes that Green Sukuk offers a viable model for integrating environmental, social, and governance (ESG) objectives into Islamic finance, advancing both ethical and ecological accountability.